OF FACIAL SOFT TISSUE - Niyozxojayev Mirzaxoja Xakimxoja ugli (Web of Journals Publishing, 2025)
Keloid scars are injuries, surgery interventions, burns or other skin from injuries then appearance to be pathological fabric They are physiological. from scars different accordingly too much outside collagen gathering with characterized and healthy tissues from the border out Especially the face in the field keloids aesthetic point from the point of view serious problem is considered, because they external to look breaks and psychological discomfort gives birth.